2016
DOI: 10.3402/ljm.v11.31689
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal bone height of exclusive narghile smokers compared with exclusive cigarette smokers

Abstract: ObjectiveTo compare the periodontal bone height (PBH) of exclusive narghile smokers (ENS) with that of exclusive cigarette smokers (ECS).MethodsTunisian males aged 20–35 years who have been ENS for more than five narghile-years or ECS for more than five pack-years were recruited to participate in this comparative cross-sectional study. Information about oral health habits and tobacco consumption were gathered using a predetermined questionnaire. Plaque levels were recorded in four sites using the plaque index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…Interestingly, the results showed no statistically significant difference in these periodontal inflammatory parameters among WSS and cigarette smokers (Javed et al, 2016a). Similar results were reported by Khemiss et al (2016) on periodontal inflammatory parameters among WSS and cigarette smokers. Results of an experimental study by Walters et al (2017) showed that light waterpipe usage is associated with epigenetic changes and related transcriptional modifications in the investigated the effect of WS on DNA methylation of the small airway epithelium; a pathologic characteristic also manifested in cigarette smokers (Buro-Auriemma et al, 2013).…”
Section: Introductionsupporting
confidence: 90%
“…Interestingly, the results showed no statistically significant difference in these periodontal inflammatory parameters among WSS and cigarette smokers (Javed et al, 2016a). Similar results were reported by Khemiss et al (2016) on periodontal inflammatory parameters among WSS and cigarette smokers. Results of an experimental study by Walters et al (2017) showed that light waterpipe usage is associated with epigenetic changes and related transcriptional modifications in the investigated the effect of WS on DNA methylation of the small airway epithelium; a pathologic characteristic also manifested in cigarette smokers (Buro-Auriemma et al, 2013).…”
Section: Introductionsupporting
confidence: 90%
“…Moreover, the age of the 72 recruited students [mean ± SD (minimum–maximum) = 23 ± 4 (20–29) years] was similar to the previous reported of a local study analyzing smoking behavior among Tunisian students [ n  = 378, age mean ± SD (minimum–maximum) = 22 ± 2 (1929) years]. [39] Almost all students have similar socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, waterpipe smokers exhibited higher dental plaque scores compared to non‐smokers . One study found no difference in toothbrush between cigarettes smokers and waterpipe smokers while another reported less frequent dental visits reported by waterpipe smokers . One of the limitations of the studies was that the specific microbial composition between groups (waterpipe smokers vs non‐smokers) was not determined.…”
Section: Effect Of Waterpipe Tobacco Smoking On Oral and Systemic Heamentioning
confidence: 98%
“…Similar to the negative biological effects of conventional cigarettes on the oral mucosa, WTS is also associated with several conditions within the oral cavity including impaired inflammatory responses, susceptibility to candida infections, periodontal diseases, dry socket, premalignant lesions and oral cavity cancer (Table ) . Although the number of studies is still limited, WTS has been consistently associated with increased prevalence of periodontal disease as measured by increased periodontal pocket depth, loss of clinical attachment and vertical bone defects compared to non‐smokers . While periodontal disease severity tends to increase in waterpipe smokers, similar to cigarette smoking, WTS also results in decreased gingival bleeding .…”
Section: Effect Of Waterpipe Tobacco Smoking On Oral and Systemic Heamentioning
confidence: 99%
See 1 more Smart Citation